Historic introduction to innate immunity - Herwald, Heiko; Egesten, Arne (Henry Stewart Talks, 2013)
Basics of innate immunity, Pioneer researchers, Groundbreaking scientific discoveries, Epidemic outbreaks, Infectious diseases